Interests and personality matter in the choice of teacher education program - Leichner, Nikolas; Ottenstein, Charlotte; Weis, Susanne; Schmitt, Manfred; Lischetzke, Tanja (Frontiers in Education, 2024)
In this paper, we examined whether it is possible to predict German teacher students' study specialization (i.e., type of school) from data on their personality (in terms of the Big Five) and vocational interests (in terms of the RIASEC model) using multinomial logistic regression. Gender and intelligence were included as control variables. Two studies are reported. The first study (N = 1,145 teacher students) took place at a German university, while Study 2 used data from the German National Education Panel Study (NEPS; data from N = 944 teacher students). In both studies, it was found that the model fit increased significantly after adding personality and vocational interests as predictors (compared with a baseline model containing only gender and intelligence as predictors). Findings show that the model of vocational interests and the Big Five personality model can be used to differentiate between teacher students with different specializations. In the long run, results like these could be used in the field of counseling to help clients who are determined to become a teacher but unsure about which specialization might be most appropriate for them. Feldfunktion geändert Formatiert: Deutsch (Deutschland) Formatiert: Deutsch (Deutschland) Feldfunktion geändert Formatiert: Deutsch (Deutschland) Formatiert: Deutsch (Deutschland)